Meningkatkan Kesadaran Masyarakat Tentang Tabungan Syariah Melalui Edukasi Cerdas Finansial Islami Di Desa Tiganderket, Kecamatan Tiganderket, Kabupaten Karo - Ikhwanul Khair; Amelia Sri Ningsih; Farhan Syafiq; Ikram Muharril; Sokon Saragih (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service program aims to increase financial literacy and awareness of sharia savings among the people of Tiganderket Village, Karo Regency, North Sumatra through the Islamic Smart Financial Education initiative. This activity was motivated by the low level of understanding of Islamic finance in rural areas, the strong dependence on conventional financial systems, and the growing practice of interest-based lending that is not aligned with Islamic principles. The program applied the Participatory Action Research (PAR) approach to encourage active participation of the community in learning processes through interactive lectures, discussions, and evaluation of knowledge before and after the activity. The results showed a significant improvement in participants’ understanding of sharia savings, which increased from 35% to 90% after the activity. Furthermore, around 60% of participants expressed interest in opening an account at an Islamic financial institution following the education session. The presence of Islamic banking representatives during the program also strengthened the connection between the community and sharia financial service providers. These findings indicate that participatory and communicative Islamic financial education is effective in improving sharia financial literacy in rural communities and may serve as a sustainable empowerment model for strengthening Islamic economic practices in Indonesia.